Pernikahan Siri dalam Tinjauan Hukum Islam dan Undang-Undang Nomor 1 Tahun 1974 Tentang Perkawinan - Farid Pardamean Putra Irawan; Nur Rofiq (Jurnal Iqtisad, 2021)
Marriage is an agreement between a man and a woman to form a family and live together until the end of life. In Islam, unregistered marriage is known as a marriage that is legally valid in religion but not under state law. Siri marriage is very thick and inherent in practice in Islamic societies which tend to still think that religiously validity is sufficient, without the need for registration by the state as a legal marriage as stipulated in Law Number 1 of 1974 concerning Marriage. The purpose of this research was carried out to try to examine in more depth the connection between siri marriage in the view of Islamic law and state law. The method used in this research is normative legal research or library research by examining document studies, namely using various secondary data such as statutory regulations, court decisions, legal theory, and it can be in the form of the opinions of scholars. This type of normative research uses qualitative analysis by explaining existing data in words or statements not with numbers. From the results of the research carried out, it was explained that carrying out a siri marriage is allowed by the state but with the consequence the power of law in solving problems due to the siri marriage.